INVESTIGATION ON PRECIPITATIONS AND DEFECTS OFTHE Fe-24Cr-2Si-0.8Mn FERRITIC SUPER ALLOY STEEL - Mohammad Dani; Parikin Parikin; R. Iskandar; A. Dimyati (Jurnal Sains Materi Indonesia, 2017)
Investigation on Precipitations and Defects of the Fe-24Cr-2Si-0.8Mn Ferritic Super Alloy Steel. A ferritic Fe-24Cr-2Si-0.8Mn alloy was produced from granular ferro-scrap, ferrochrome, ferrosilicon and ferromanganese in a conventional induction furnace. The alloy is dedicated for application as structure material in high temperature devices, such as nuclear reactor vessel and heat exchanger. The alloy has been verified to have high tensile strength and high resistant against corrosion. The aim of this work is to study the microstructures, chemical compositions and precipitation occurred inside grain and grain boundary of the alloy, to obtain more information of its superior physical-chemical properties. STEM-EDX mappings reveal the present of relatively large aluminum oxide, silicon carbide and high oxygen and high carbon containing precipitations on the specimens. The grains that were formed, exhibit relatively strong deformations as obviously shown by the elongated grains and sub-grains with typical high density of dislocations, even though, less mechanical treatments applied. Small porosities are also present homogeneously separated on the whole view area.